High-Efficiency Partial Power Converter for Integration of Second-Life Battery Energy Storage Systems in DC Microgrids - Naser Hassanpour; Andrii Chub; Neelesh Yadav; Andrei Blinov; Dmitri Vinnikov (IEEE Open Journal of the Industrial Electronics Society)
This article presents a power electronic interface for battery energy storage integration into a dc microgrid. It is based on a partial power converter (PPC) employing a current-fed dc–dc topology. The article provides an analysis of application requirements and proposes an optimal second-life battery stack configuration to leverage all the benefits of the PPC technology. This converter can regulate current at zero series voltage between a battery stack and a dc microgrid using the topology morphing control. The article shows how the converter and its control system should be designed to operate in a droop-controlled dc microgrid. The experimental results demonstrate the converter's capability to operate under droop control, implementing both voltage step-up and -down regulation with a smooth transition between converter modes. The experimental efficiency reaches as high as 99.45%, demonstrating an efficient approach for second-life battery energy storage integration into dc microgrid.